Risk Taking Behavior of Adolescents in Indonesia (Country Report) - Moersintowati Narendra; Parwita S. Basuki; Lestari B. Soeharjono; Endang W. Ghozali (Paediatrica Indonesiana, 1990)
Adolescent problems in Indonesia are becoming more und more relevant due to the increasing reports recently. Although data gathered are very limited a certain consideration should be well planned to get all resources in terms of motivation in paying more attention to the future of Indonesia youth problems such as narcotics/ drug abuse, sexual activities including sexual transmitted diseases etc. A good communication with the other Aseafl countries in controlling those risk taking behaviors in adolescent will be very premising to gain the improvement of people's life quality by the year 2.000.